The politics and practice of initiating a public health postgraduate programme in three universities in sub-Saharan Africa: the challenges of alignment and coherence - Woldekidan Kifle Amde; David Sanders; Mohsin Sidat; Manasse Nzayirambaho; Damen Haile-Mariam; Uta Lehmann (BMC, 2020)
Abstract Background In-country postgraduate training programme in low and middle income countries are widely considered to strengthen institutional and national capacity. There exists dearth of research about how new training initiatives in public health training institutions come about. This paper examines a south-south collaborative initiative wherein three universities based in Ethiopia, Rwanda and Mozambique set out to develop a local based postgraduate programme on health workforce development/management through partnership with a university in South Africa. Methods We used a qualitative case study design. We conducted semi-structured interviews with 36 key informants, who were purposively recruited based on their association or proximity to the programme, and their involvement in the development, review, approval and implementation of the programme. We gathered supplementary data through document reviews and observation. Thematic analysis was used and themes were generated inductively from the data and deductively from literature on capacity development. Results University A successfully initiated a postgraduate training programme in health workforce development/management. University B and C faced multiple challenges to embed the programme. It was evident that multiple actors underpin programme introduction across institutions, characterized by contestations over issues of programme feasibility, relevance, or need. A daunting challenge in this regard is establishing coherence between health ministries' expectation to roll out training programmes that meet national health priorities and ensure sustainability, and universities and academics' expectations for investment or financial incentive. Programme champions, located in the universities, can be key actors in building such coherence, if they are committed and received sustained support. The south-south initiative also suffers from lack of long term and adequate support. Conclusions Against the background of very limited human capacity and competition for this capacity, initiating the postgraduate programme on health workforce development/management proved to be a political as much as a technical undertaking influenced by multiple actors vying for recognition or benefits, and influence over issues of programme feasibility, relevance or need. Critical in the success of the initiative was alignment and coherence among actors, health ministries and universities in particular, and how well programme champions are able to garner support for and ownership of programme locally. The paper argues that coherence and alignment are crucial to embed programmes, yet hard to achieve when capacity and resources are limited and contested.